Crustal thickness and magma storage beneath the Ecuadorian arc. (October 2021) - Koch, Clinton D.; Delph, Jonathan; Beck, Susan L.; Lynner, Colton; Ruiz, Mario; Hernandez, Stephen; Samaniego, Pablo; Meltzer, Anne; Mothes, Patricia; Hidalgo, Silvana
Abstract: The Northern Andes of Ecuador contain some of the most active volcanic systems in the Andes and extend over a broad region from the Western Cordillera to the Subandean Zone. While it is known that the arc straddles a range of basement compositions, from accreted mafic oceanic terranes in the west to silicic continental terranes in the east, the details of the crustal structure beneath the arc is unclear despite being critical for understanding magmatic and tectonic processes in this portion of the Andes. To gain insight into these processes, we create two 3D models of crustal and upper mantle seismic properties throughout the region. The first highlights the discontinuity structure using receiver functions, which allows for the recovery of crustal thickness beneath the Ecuadorian Andes. We observe a range from ~50 to 65 km under the high elevations, with thicker crust beneath the lower elevation Western Cordillera compared to the higher elevation Eastern Cordillera. This can largely be explained by density variations within the crust that are consistent with observed terranes at the surface, implying these terranes extend to depth. The second model combines our receiver functions with Rayleigh wave dispersion data from ambient noise measurements in a joint inversion to construct a 3-D shear wave velocity model. This model shows several mid-crustal (5–20 km below sea-level) low velocity zones beneath Ecuadorian arc volcanoes that contain a maximum of ~14% melt. These low velocity zones likely represent zones of long-term magma storage in predominantly crystalline reservoirs, consistent with "mush zones". Furthermore, the depth of the inferred reservoirs below several of the volcanic centers (e.g., Chiles-Cerro Negro and Tungurahua) are in broad agreement with previous geobarometry and geodetic modeling. Our results provide new observations of possible long-term magma reservoirs below other less-studied volcanic systems in the Ecuadorian arc as well, and further contributes to a mounting number of observations indicating long-term magma storage at low melt percentages in the mid-crust beneath active arc systems.